Transformational leadership and its functionality in arts organization - Qistina Donna, Lee Abdullah; Varatharajoo, Kashini Devi (UNIMAS Publisher, 2017)
Throughout the eyes of the world, an organization may have a great identity. However, without a leader with proper functionality in managing the organization, it is certain that the organization might face failure in the future. In addition to that, in this fast-paced world of competition and challenges, an up-to-date transformation is indeed necessary for a bright future. Transformational leadership is known to stimulate followers’ performance and enhance their commitment to an outstanding level. Numerous researches have proved that practicing transformational leadership style in the management of every organization will lead to a bright competitive future but how this leadership style is practiced is rarely disclosed. In the conjunction to this, the researcher analyzed further on the functionality of transformational leadership concept or style in the organization. Mix method of qualitative and quantitative was employed through structured questions targeted to the main executives of ASTRO. The final outcome of the survey based on the conceptual framework was suggested to the firm to be implemented. Thus, there are three aspects where the functionality is reflected which are Exerting influence on subordinates with Idealized influence, Open and imaginative with Intellectual stimulation, as well as Idealized influence and Intellectual stimulation.